2002
DOI: 10.1159/000063714
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Eccrine Glands of the Foot Pads of the Rock Hyrax (<i>Procavia capensis</i>, Hyracoidea, Mammalia)

Abstract: In order to find correlations between skin gland morphology and specific ethological features, the cutaneous glands of the foot pads of Procavia capensis were studied by histological and various histochemical methods and by electron microscopy. In the foot pads, abundant specific eccrine skin glands occur, which consist of coiled tubular secretory portions and coiled ducts. The wall of the secretory part is composed of cuboidal glandular cells and myoepithelial cells. Among the glandular cells two types occur:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(31 reference statements)
0
12
1
Order By: Relevance
“…This observation compares to findings on this gland type in the foot pads of other carnivores and of hyraxes (e.g. Meyer and Bartels 1989;Stumpf and Welsch 2002;Yasui et al 2004Yasui et al , 2005a, but less to those achieved from such glands in the nasolabial region of ruminants (Tsukise et al 1988b;Yasui et al 2005c). Additionally, the dark cells of the raccoon nasolabial glands appeared to contain higher numbers of secretory granules, than such glands in the digital pads of this species (Yasui et al 2004(Yasui et al , 2005a.…”
Section: Discussioncontrasting
confidence: 56%
“…This observation compares to findings on this gland type in the foot pads of other carnivores and of hyraxes (e.g. Meyer and Bartels 1989;Stumpf and Welsch 2002;Yasui et al 2004Yasui et al , 2005a, but less to those achieved from such glands in the nasolabial region of ruminants (Tsukise et al 1988b;Yasui et al 2005c). Additionally, the dark cells of the raccoon nasolabial glands appeared to contain higher numbers of secretory granules, than such glands in the digital pads of this species (Yasui et al 2004(Yasui et al , 2005a.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous research has demonstrated that human native eccrine sweat glands express cytokeratins, EMA, CEA, α-SMA, Na + -K + -ATPase, Na + -K + -2Cl-cotransporter, and so on, with myoepithelial cells expressing CK5, CK7, CK14, CK17, vimentin and Į-SMA, ducts expressing CK1, CK5, CK10, CK11, CK14 and CK19, and secretory cells expressing CK7, CK8, CK18 and CK19 (Eckert et al 1992;Schon et al 1999;Saga 2002;Stumpf and Welsch 2002;Li et al 2009). Our tubular-like structures express P-CK, CK5, CK7, CK14, CK19, α-SMA and CEA, and the localization of these proteins is similar to that seen in native human eccrine sweat glands, demonstrating that the Matrigel-embedded tubular-like structures are reconstituted eccrine sweat glands.…”
Section: Matrigel-embedded Eccrine Sweat Gland Cells Form Tubular-likmentioning
confidence: 99%
“…In human tissues, eccrine glands do not express lysozyme, but apocrine glands may have a bactericidal function (Campbell et al 1982;Ezoe and Katsumata 1990) by expressing lysozyme. As in Echinops the eccrine glands of Procavia also express lysozyme and defensin (Stumpf and Welsch 2002). Both proteins may have a synergistic effect in their antibacterial activity.…”
Section: Secretory Functionsmentioning
confidence: 99%
“…This cytokeratin is expressed mainly in socalled simple epithelia, including human mammary epithelium and apocrine cutaneous gland epithelium of the human axilla (Moll et al 1982), and was also found in eccrine glands of the relatively primitive hyrax Procavia (Stumpf and Welsch 2002). In apocrine skin glands, e.g., impala (Welsch et al 1998a) and aardwolf (Stöckelhuber et al 2000), the distribution of the immunoreactivity of CK14 and CK19 within the secretory cells is usually different from that of the eccrine glands of Echinops.…”
Section: Lectin-bindingmentioning
confidence: 99%